1986
DOI: 10.1111/j.1365-2125.1986.tb05231.x
|View full text |Cite
|
Sign up to set email alerts
|

Sparteine oxidation polymorphism: a family study.

Abstract: 1 Polymorphic oxidation of the pharmacogenetic probe drug sparteine was investigated in 35 parents and 29 siblings of 20 unrelated poor metabolizer (PM) probands. Phenotyping was carried out on the basis of metabolic ratio (MR) = sparteine/dehydrosparteines in the 12 h urine. The distribution of MR was bimodal: 47 relatives (20 siblings and 27 parents) had MR ranging from 0.22-12 and were defined as extensive metabolizers (EM) whereas MR ranged from 20-340 in nine siblings and eight parents thus defined as PM.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The frequency of PM was 6/185 = 3.2% compared with 7.3% found in 301 Danes (Br0sen et al, 1985) (p = 8.8%, Fischer's exact test). As in the Danes (Br0sen et al, 1985(Br0sen et al, , 1986a, the sparteine test could not distinguish the two genotypes within the dominant phenotype. Comparative studies of families and populations (Evans et al, 1983;Br0sen et al, 1986a) have indicated that sparteine oxidation on the average is faster in homozygous dominants than in heterozygotes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency of PM was 6/185 = 3.2% compared with 7.3% found in 301 Danes (Br0sen et al, 1985) (p = 8.8%, Fischer's exact test). As in the Danes (Br0sen et al, 1985(Br0sen et al, , 1986a, the sparteine test could not distinguish the two genotypes within the dominant phenotype. Comparative studies of families and populations (Evans et al, 1983;Br0sen et al, 1986a) have indicated that sparteine oxidation on the average is faster in homozygous dominants than in heterozygotes.…”
Section: Discussionmentioning
confidence: 99%
“…In Caucasians, two phenotypes are clearly separated: poor metabolizers (PM) who make up 7-9% of the population and extensive metabolizers (EM) who make up the rest (Vinks et al, 1982;Evans et al, 1983;Eichelbaum & Woolhouse, 1985;Br0sen et al, 1985). The PM phenotype is inherited as an autosomal Mendelian recessive trait, whereas the EM phenotype comprises both heterozygotes and homozygous dominants (Evans et al, 1983;Br0sen et al, 1986a).…”
Section: Introductionmentioning
confidence: 99%
“…A distinct isozyme of cytochrome P450, P450dbl, catalyses the oxidation of sparteine and debrisoquine, and recent studies (Gonzalez et al, 1988;Zanger et al, 1988) have shown that P450dbl is missing in the livers of some PM. Family studies showed that PM are homozygotes for a recessive autosomal gene (Br0sen et al, 1986a;Evans et al, 1980Evans et al, , 1983. The sparteine/ debrisoquine oxidation polymorphism is a major determinant of the elimination of more than 20 drugs in current use, with implications for the clinical use of antidepressants, some neuroleptics and some antiarrythmics (Br0sen & Gram, 1989a).…”
Section: Introductionmentioning
confidence: 99%
“…The 35 parents and 20 siblings of 20 out of the 22 poor metabolizers were also phenotyped [8] , and the pedigrees confirmed that poor metabolism is inherited in an autosomal recessive trait. In two subsequent studies also using sparteine to probe for CYP2D6 in 358, 327 and 278 healthy subjects, respectively [9 -11] ( Figure 2 ), there were 33 (9.2%), 27 (8.3%) and 28 (10.1%) poor metabolizers, respectively.…”
Section: Introductionmentioning
confidence: 54%
“…In a subsequent population study, there were only three poor metabolizers out of 327 subjects (0.92%) [8] . These figures are in keeping with other European populations [25] .…”
Section: The Cyp2c19 Oxidation Polymorphism In the Danish Populationmentioning
confidence: 98%